Análise do potencial de utilização de energia solar para a área urbana da cidade de Cuiabá – MT - Magalhães, Natália Amorim (2020)
The capital of Mato Grosso, Cuiabá, as well as the rest of the state, presents intense climatic conditions throughout the year. A city with a hot climate and a predominantly sunny sky all year round, Cuiabá has great potential for the deployment of photovoltaic solar energy, despite not being located in the area of Brazil that receives the most radiation. This study has the general objective of analyzing this potential, considering the importance of using renewable energies in the current scenario and the increased demand for electricity in Brazil. For this purpose, as specific objectives, the analysis was carried out using irradiation data from the SunData software, both in the horizontal plane and in the ideal inclined plane for power generation, and by the data from the fixed station of the Postgraduate Program in Environmental Physics (PGFA), located at the Porto region, in Cuiabá, MT and from them the capacity factor of two solar panels was calculated, chosen based on quality and good cost benefit criteria, for irradiation incident in the urban area of Cuiabá, MT. In addition, an analysis of the potential on the microclimate scale was performed based on 3D modeling generated by the Autodesk Revit software in conjunction with the Insight Analysis plugin. Therefore, photovoltaic solar energy is advantageous, since the plates chosen in the study obtained a capacity factor average greater than 15.1%, in addition it complements the energy produced by hydroelectric plants and other sources, relieves the increase in peak demand of energy during the day, it does not generate emissions in the electric energy production process, yet it does not use fuels, reducing its generation cost.